(untitled) (Biological Sciences - PJSIR, 1998)
The phenylhydrazino derivatives of ethyl acetoacetate (1), acetyl acetonitrile (11) and acetylacetone (17) reacted with malononitrile, malononitrile dimer (4a) or ethyl cyan acetate dimer (4b). The products were treated with benzaldehyde to yield different polyfunctionally substituted pyridopyridines and pyridopyri- dazines.